Analysis of the accuracy of different levels of resistance generated by Threshold® IMT in young obese women. (Revista horizonte, 2013)
This article analyzes the accuracy of the Threshold® IMT in the determination of different levels of resistance: R1=7, R2=15, R3=21, R4=27, R5=35 and R6=41 cm H2O in young obese women, taking maximum inspiratory pressure (MIP) as a reference. METHODS: For this purpose, 21 obese grade I women, with BMI of 34.56 ± 5.82 kg/m2 and mean age of 44.4 ± 13.4 years were subjected to MIP measurement through the manometer with subsequent measurement of resistance levels generated by the Threshold® IMT of R1=7, R2=15, R3=21, R4=27, R5=35 and R6=41 cm H2O. For the normality test, the Shapiro-Wilk test was applied, and for the analysis between the percentages of MIP obtained and the different resistances generated by Threshold® IMT test, the ANOVA test and repeated measures with the Bonferroni post-hoc significance level of p